Reconfigurability in manufacturing system: advancing the flexibility and productivity - Abdul Rahman, Azrul Azwan; A. Rahman, Muhamad Arfauz (Penerbit UTeM Press, 2023)
This book aims to advance the field of reconfiguration in the manufacturing industry, particularly in the context of Industry 4.0. It focuses on embedding reconfigurability in manufacturing systems to enable the industry to adapt to future changes and improve production outcomes. Configuration engineers deal with virtually every system and part in the factory, involved in all phases of manufacturing systems, including measurement, diagnosis, therapy, repair, and patient management. They design, develop, make, and manage systems in various settings, including laboratories, design departments, and manufacturing plants. The field of reconfiguration engineering is not the sole domain of practitioners and educators, and there is a need to bridge gaps between the application of mechanical engineering knowledge and electrical engineering knowledge. The book is written in a logical and coherent manner to provide a working knowledge of the important details of reconfiguration in the manufacturing industry, aiming to provide easy understanding of best practices in this field.